IDENTIFICATION AND EXPLANATION OF THE FACTORS RELATED TO KNOWLEDGE MANAGEMENT IN SUPREME AUDIT COURT - Farokhian, Abdolmajid; Tavakoli, Hamdolla; Salajegheh, Sanjar (Revista Inclusiones, 2019)
The purpose of this study is to identify and explain the factors related to knowledge management. The present research is applied in the field of applied research. It is a descriptive research and survey method based on a questionnaire tool. In this research, firstly, through the study of previous studies and studies, a relatively comprehensive understanding of the literature in this field was obtained and, accordingly, a preliminary list of knowledge management factors as well as its components and indicators were provided. Then these factors were completed and finalized using content analysis and Delphi methodology. The statistical population of this research, in the Delphic Phase, 30 experts and at the stage of factor analysis, 199 managers Court of Auditors in different categories. The findings of the main components analysis using one-sample t-test and Chi-square test showed that the factors related to knowledge management include leadership, culture, technology, education, human resources, activities and processes, and infrastructure. After confirming the relationship of each of these factors with knowledge management, using Pearson correlation coefficient, we have provided practical suggestions for improving and improving knowledge management.